ASSESSMENT OF ECOSYSTEMS SERVICES FOR SUSTAINABLE DEVELOPMENT AND LAND USE MANAGEMENT - Konstantinova, Elīna; Brūniņa, Līga; Peršēvica, Aija; Živitere, Marga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
A very important factor for sustainable development is a balance between the exploitation of natural resources for socio-economic development, and conserving ecosystem services that are critical to everyone’s wellbeing and livelihoods. The strategical importance of ecosystem services is set by the UN Millennium Ecosystem Assessment in 2005, which put ecosystem services firmly on the policy agenda and the EU Biodiversity Strategy, which states that “Member States must map and assess the state of ecosystems and their services in their national territory by 2014, assess the economic value of such services, and promote the integration of these values into accounting and reporting systems at EU and national level by 2020”. The aim of the paper is to present and discuss the approach of ecosystem services assessment for sustainable land use and strategical development scenarios. The paper will focus on the role of ecosystem services in development and spatial planning, and this approach can be integrated in planning processes and decision making. There will be presented a case study for two coastal territories in Latvia, where an ecosystem services assessment was implemented and sequentially different development scenarios considered and analysed.